Perlindungan Hukum Terhadap Korban Kekerasan yang Dilakukan oleh Penyidik (Pandecta Research Law Journal, 2019)
Crime is an act that violates the prohibitions set out in the rule of law, and does not fulfill or go against the orders set out in the rules of law that apply in society. For human interests to be protected, laws must be implemented in accordance with applicable regulations. However, there are often violations of the law, even at the level of law enforcement officials themselves. The Criminal Procedure Code does not explicitly regulate sanctions for law enforcement officials who commit violence or other practices that violate the provisions therein. The method used is juridical normative to explain sanctions for law enforcement officers who violate the Criminal Procedure Code in dealing with crime.Crime is a prohibition set out in the rule of law, and is not in accordance with the orders set out in the rule of law that applies in society. For human interests to be protected, laws must be applied in accordance with applicable regulations. However, various lawsuits were dropped, even at the level of law enforcement itself. The Criminal Procedure Code (Indonesian : KUHAP)does not emphasize sanctions for law enforcement officials who commit violent practices or other practices that conflict with the provisions therein. The purpose of this study is to study law enforcement sanctions that are against the Criminal Procedure Code (KUHAP) in dealing with crime.